PERSEPSI PEGIAT JENDER TERHADAP KONSEP PASAL 31 AYAT (3) UNDANG-UNDANG PERKAWINAN TENTANG STATUS KEPALA KELUARGA - Prihatinah, Tri Lisiani (Faculty of Law, Universitas Jenderal Soedirman, 2011)
Some of gender activists assume that status of husband as a head of household is discriminating wife. Therefore, they propose a gender equality model which gives the same status to both husband and wife as a head of household altogether. By using sociological method and feminist legal analysis, it is resulted that most gender activists who become the source of information in this research do not agree with the proposed model of gender equality because they do believe its legal consequence will burden more to the wife. However, they agree that women develop their economic ability to ear money. These gender activists do not want to amend Article 31 (3) Law Number 1 Year 1974. They understand this article as a reflection of substantive equality which recognizes husband as a head of household’s status is parallel with the burden of the responsibility.